PENGARUH WORKING CAPITAL TURNOVER, CASH TURNOVER, INVENTORY TURNOVER DAN CURRENT RATIO TERHADAP PROFITABILITAS (ROA) PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - MARLINA WIDIYANTI; SAMADI W BAKAR (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The aim of this research is to know the influence of independent variables WCTO, CTO, ITO and CR to dependent variable profitability (ROA), either partially or simultaneously. The object of this research are Property and Real Estate companies listed in Indonesian stock exchange period 2008-2012. Samples for this research consists of 9 companies, purposive sampling method used in this research. The analysis technique used multiple linear regression. The result shows that working capital turnover do not have influence to profitabilty (ROA), cash turnover give positive and significant influence to profitablity (ROA), inventory turnover give positive and significant influence to profitability (ROA), and current ratio do not have influance to Profitability (ROA). Simultaneously, working capital turnover, cash turnover, inventory turnover and current ratio have a influence to profitability (ROA) with percentage of contribution 45,1%. It could be concluded 45,1% independent variables have influence to dependent variable.